(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
This article is about analysis of the manager’s competences and also about influence of these competences on the organization X. Manager which has knowledge, experience, and communication skills is influencing the level of integration, involvement, and quality of the staff’s work in a positive way. Thanks to the final research, which was based on the interview with the owner and manager of "small and medium company", we had proven that competences gained from one source might be filled with the others.